Handbook of Gas Sensor Materials : Properties, Advantages and Shortcomings for Applications Volume 2: New Trends and Technologies. - Korotcenkov, Ghenadii (New York, NY : Springer, 2013)
This volume offers a detailed coverage of materials for gas sensors, including the properties and relative advantages of various materials. It provides an understanding of the fundamentals of sensor functioning as well as information about applications.
References -- About the Author -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Gas detectors -- Materials -- Handbooks, manuals, etc; Electronic books